Analysis of the State Civil Apparatus's Public Service Performance at the Pinaesaan Village Office, Wenang District - Steven Monggesang; Daud M. Liando; Donald K. Monintja (Journal of Public Administration and Government, 2023)
The provision of services to the community by service providers in line with set norms that attempts to fulfill the demands and needs of the community is referred to as public service performance of the state civil apparatus. The goal of this study is to use qualitative research methodologies to assess the work of state civil officials at the Pinaesaan Village office in Wenang District. The data were gathered by watching and interviewing the pre-selected informants. Six persons served as research informants: the Lurah, the kelurahan secretary, the Head of the Public Service Section, and three members of the community. This study lasted three months, from April to June. Following data collection, the data were analyzed using Miles and Huberman's (1984) data analysis method model, which was divided into three activities: data reduction, data presentation, and conclusions or verification. The study's findings indicate that the performance of public services for the state civil apparatus in the Pinaesaan sub-district of the sub-district's authority has been carried out based on standard components of public services but has not been maximized in its services, particularly in terms of handling and complaints of suggestion boxes. accept suggestions and complaints of community services given by civil servants.